Cisco CCNP ENARSI v1.1 (300-410) Cert Prep: 2 VPN Technologies. - Wallace, Kevin (linkedin.com, 2020)
Study for the second domain of the Cisco ENARSI certification exam: VPN Technologies. Learn about troubleshooting routing protocols such as EIGRP, OSPF, and BGP.